Improving Students’ Reading Comprehension by Using Concept Oriented Reading Instruction (CORI) Strategy - Mita Lianah; Nina Juwita Sari (Linguistic, English Education and Art (LEEA) Journal, 2020)
ABSTRACT The purpose of this research are to know the improvement of students reading comprehension by using CORY strategy. This research used Classroom Action Research (CAR), because CAR is aimed to got an improvement in teaching process. In this research have two cycle to know the improvement of students reading comprehension.Each cycle consisted of two meeting. Each meeting has equal to 2x40 minutes. Each cycle of the research consisted of four steps, they are planning, action, observation and reflection. The subject of this research was the ninth grade which is consists of 20 students. The object of this research was reading comprehension. Based on the data that had been collected from pre test to cycle I, and cycle I to cycle II there were improvement. The researcher had found some progress on the scores of the students. The result of pre-test showed there were 3 students or 15% reach KKM. In the cycle I, there were 10 students or 50% of students reach KKM’s score. Meanwhile, in cycle II there were 15 students or 75% of all the students number who reach the KKM. Keyword: Students` Reading Comprehension, CORI